Psychological Security during Coronavirus Pandemic for a sample of University of Jeddah Students - Alhaj Mahmoud, Ferial Mahmoud (Dirasat: Educational Sciences, 2023)
Objectives: The study aimed to reveal the level of psychological security during Corona pandemic period for a sample of the University of Jeddah students. Methods: To achieve the goal of the study, a scale consisting of (33) items was constructed according to item response theory, specifically according to the rating scale model. The researcher used the following programs: (SPSS), (BIGSTEPS), and (BIOLOG-MG3) in analyzing the data of this scale, which was applied to a sample of (612) students from the University of Jeddah. During the first semester of the academic year (1441-1442 AH), corresponding to (2020-2021 AD), each of the following were estimated: psychological security scale parameters, the standard error of estimate, and items fitting to the rating scale model Results: In light of the results of model fitting, the psychological security scale consisted in its final form of (25) items. Also the results showed that the scale has good psychometric properties. Conclusion: Depending on the results, it becomes clear that the level of psychological security during the Corona pandemic was high among the students of the University of Jeddah.